Community Marginalization as the Effect of Public Policy in Democratic Governance Era - Suharto, Didik G; Botha, Hendrikus H.; Haryanti, Rina H.; Wahyunengseh, Rutiana D. (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Watu Ata natural reserve is a natural reserve located in Ngada of Nusa Tenggara Timur Province. Watu Ata natural reserve was established based on Ministry of Forestry’s Decree Number 432/Kpts-II/92. The policy impacts negatively on community marginalization, particularly the elimination of people from their previous cultivated land. This research aimed to analyze the community marginalization occurring as a result of the policy establishing Watu Ata forest area to be conservation area functioning as natural reserve. This research was conducted in two villages namely Inelika Village and Heawea Village. The research method employed was qualitative one with descriptive approach. The type of data used is primary and secondary data. Sampling technique employed was purposive sampling one. Techniques of collecting data used were interview, observation, and documentation. Technique of analyzing data used Miles and Huberman’s data analysis technique (data reduction, data presentation, conclusion drawing and verification). The result of research showed that: 1) the form of marginalization the people felt surrounding Watu Ata natural reserve area was social exclusion from cultivated land. Social exclusion from cultivated land encountered by the people in Heawea and Inelika Villages impacts on other exclusion forms. 2) the attempt the people had taken to deal with marginalization was to establish an organization called PERMATA (Perhimpunan Masyarakat Watu Ata or Watu Ata People Association). The objective of getting fair distribution of forest resource and property certainty has not been achieved yet until today. In democratic governance era, government policy is ideally a dialogical product, government with community.